Exercise training as a standard part of oncological therapy Sport als integraler Bestandteil der onkologischen Therapie - Heinicke, V.; Spanier, B.; Von Korn, P.; Halle, M. (Gastroenterologe, 2019)
Exercise training should be implemented for every cancer patient as a standard part of the oncological therapy regime. Patients benefit from structured exercise training by increasing fitness, muscular strength and improving fatigue and quality of life. Cohort studies showed an even better survival for active colorectal patients compared to inactive patients. Randomized, controlled studies are missing. General recommendations for cancer patients include 150 min of moderate aerobic activity and resistance training twice a week. For the most cancer patients—especially under therapy—these recommendations are too high concerning duration and intensity. Individual recommendations must be adapted to the fitness level of each patient. Starting with short durations of exercise and light intensity and increasing first the duration of each training session and later intensity by time. Especially older patients benefit from a supervised exercise setting for example in physiotherapy units or in sports groups for cancer patients. A structured exercise program is considered as a safe supportive therapy.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Colorectal cancer; Individual training; Physical activity; Prognosis; Quality of life